2020
DOI: 10.1093/neuros/nyaa354
|View full text |Cite
|
Sign up to set email alerts
|

Altered Motor Excitability in Patients With Diffuse Gliomas Involving Motor Eloquent Areas: The Impact of Tumor Grading

Abstract: BACKGROUND Diffuse gliomas have an increased biological aggressiveness across the World Health Organization (WHO) grading system. The implications of glioma grading on the primary motor cortex (M1)-corticospinal tract (CST) excitability is unknown. OBJECTIVE To assess the excitability of the motor pathway with navigated transcranial magnetic stimulation (nTMS). METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Further studies are needed to investigate more deeply the relationship between presurgical plastic reorganization and functional outcomes following resection, by also taking account of the various cognitive profiles before surgery, and the tumor features, i.e., its volume, its grade (LGG vs. HGG) [99], as well as its location. Indeed, a recent TMS study showed that the preoperative excitability of the motor eloquent areas (assessed using a cortical excitability score, which evaluates the number of abnormal inter-hemispheric resting motor threshold ratios) was significantly increased in isocitrate dehydrogenase wild-type gliomas [100]. Moreover, Vergani et al [101] compared LGG in contact with the subventricular zone (SVZ) versus LGG not in contact with the SVZ.…”
Section: Preoperative Prediction Of Postoperative Functional Outcomes Based On Fni/tmsmentioning
confidence: 99%
“…Further studies are needed to investigate more deeply the relationship between presurgical plastic reorganization and functional outcomes following resection, by also taking account of the various cognitive profiles before surgery, and the tumor features, i.e., its volume, its grade (LGG vs. HGG) [99], as well as its location. Indeed, a recent TMS study showed that the preoperative excitability of the motor eloquent areas (assessed using a cortical excitability score, which evaluates the number of abnormal inter-hemispheric resting motor threshold ratios) was significantly increased in isocitrate dehydrogenase wild-type gliomas [100]. Moreover, Vergani et al [101] compared LGG in contact with the subventricular zone (SVZ) versus LGG not in contact with the SVZ.…”
Section: Preoperative Prediction Of Postoperative Functional Outcomes Based On Fni/tmsmentioning
confidence: 99%
“… No adverse events Rohde V et al, 2003 16 X 70–90% x RTM The use of intraoperative repetitive nTMS was capable of correctly identifying 92% of the primary motor cortex x Gimramov R F, 2002 21 Figure-of-eight stimulation coil x x RTM Patients with tumors in the brainstem or the motor area had higher RMT thresholds compared to healthy subjects. x Machetanz K et al, 2021 44 Figure-of-eight stimulation coil 110% X RMT/latency/amplitude Patients with apparent paresis had higher RMT than healthy patients or patients without apparent paresis. x Neville I S et al, 2021 42 x 120–140% x RMT The hemisphere with tumors presented different excitability compared to the healthy hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“… 43 Also, a study found that patients with high tumor grades had the excitability pattern of the hemisphere different from the low tumor grades patients. 44 …”
Section: Resultsmentioning
confidence: 99%
“…For example, an abnormal RMT ratio, i.e. the ratio between the RMTs of both hemispheres, can be used as a marker of disease progression, for example in patients with brain tumors (Lavrador et al 2020;Rosenstock et al 2017;Tozlu et al 2020).…”
Section: Discussionmentioning
confidence: 99%